Socio-demographic characteristics of children and young people with primary brain tumours: comparison between a public and private sector tertiary hospital in Karachi, Pakistan - Urooj, Faiza; Nida Zahid,; Brown, Nick; Martins, Russell Seth; Martensson, Thomas; Martensson, Andreas; Enam, Syed Ather (Journal of the Pakistan Medical Association, 2024)
Primary brain tumours (PBTs) are the commonest solid tumours in children and young people (CYP). A study was conducted at a private and a public sector hospital in Karachi, Pakistan, to determine the socio-demographic and tumour-related characteristics of CYP with PBTs between those presenting to the public and private hospitals. A total of 49 patients were included. The commonest PBT was pilocytic astrocytoma (29%). There were no differences in tumour-related characteristics between the two groups. However, parents of CYP with PBTs presenting to the public sector hospital were significantly less educated and had lower household incomes. No significant differences in age, gender, educational status, and ethnicity of CYP with PBTs were observed. Since CYP with PBTs presenting at the public sector hospital were from significantly lower socio-economic backgrounds and their parents were less educated, it suggests socio-economic disparities in PBT care for CYPs in Karachi, Pakistan.